Effects of agri-enviroment schemes and different farming practices on the diversity of farmland birds - Fehér, Ádám; Tóth, Bálint; Heltai, Miklós (JOURNAL OF LANDSCAPE ECOLOGY, 2015)
Farming practices that benefit biodiversity and maintain the sustainable use of natural resources play an increasing role in the Common Agricultural Policy of the EU. These requirements on arable lands and pasture fields can mostly achieved by agri-environment schemes, dissolving the land use conflicts in rural areas. The success of certain AES can be well evaluated by monitoring resident bird communities (using Farmland Bird Index). Based on the results of several European studies, we consider that AES which is focusing on semi- natural pasture conservation, food resource protection, or creating new breeding sites for songbirds can be only effective, if AES programs applied on a wider area than some isolated parcels. On the other hand, the timing and implementation of the used monitoring methods can affect the evaluation of results, as the different characteristics of land use in Europe.
Keywords: agriculture; land use; agri-environment schemes; biodiversity; songbirds; CAP